2015
DOI: 10.4103/1947-489x.210274
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards insulin therapy among patients with type 2 diabetes in Tripoli, Libya

Abstract: Background: In patients with type 2 diabetes mellitus (T2DM), failure to control of blood glucose with lifestyle modifications and oral hypoglycemic agents (OHA) leads to insulin therapy. Objectives: We aimed to 1) find out the prevalence of psychological insulin resistance among patients with T2DM and 2) explore the factors affecting and reasons behind their attitude towards insulin use. Patients and methods: In a cross sectional study, 1703 Libyan patients with T2DM on oral hypoglycemic agents (OHA) were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
5
2
Order By: Relevance
“…The perception of the type 2 diabetic participants that insulin therapy was painful and that insulin was addictive was also noted in the Libyan study[ 26 ] in which almost 50% of the participants with PIR agreed. The same result was found in the Congo[ 27 ] where the participants who refused insulin were significantly apprehensive of the pain and the possibility of being addicted as compared to those who accepted insulin.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The perception of the type 2 diabetic participants that insulin therapy was painful and that insulin was addictive was also noted in the Libyan study[ 26 ] in which almost 50% of the participants with PIR agreed. The same result was found in the Congo[ 27 ] where the participants who refused insulin were significantly apprehensive of the pain and the possibility of being addicted as compared to those who accepted insulin.…”
Section: Discussionmentioning
confidence: 69%
“…[ 16 ] A moderately low level of insulin therapy refusal (15%) was found in a Malaysian study, but[ 25 ] a very high level of unwillingness for insulin was reported in a Libyan study in which 94.6% of the participants expressed unwillingness to accept insulin therapy. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding from the logistic regression analysis showed that, people with primary and secondary education status were 45% and 42% less likely to have poor perception toward shifting OAHAs to insulin, respectively, as compared to those who were unable to read and write (P < 0.05). Similarly, studies in Libya and India found that lower education levels were associated with poor perception [ 20 , 22 ]. This is because as the literacy level increases the level of awareness about diabetes and its treatment will be improved.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, fear of injections was the most often cited excuse for not taking insulin treatment. Similarly, in a study conducted in the Caribbean nation of Trinidad, Libya, Saudi Arabia, and France among diabetes patients, the perception of painful injections was a barrier to starting insulin therapy [ 12 , [18] , [19] , [20] ]. This aspect should be properly addressed through education, particularly about insulin injection practice.…”
Section: Discussionmentioning
confidence: 99%